Detección in silico de productos naturales dirigidos a la corismato sintasa - Zaghlool Al-Khayyat, Mohammed (Innovaciencia, 2019)
Introduction: Chorismate synthase catalyzes the final step in shikimate  acid pathway involved in synthesis of aromatic compounds in bacteria.This enzyme can be a possible molecular target for design of antibiotics. Materials and Methods: Homology modeling and molecular dockingwere performed to screen about one hundred natural compounds in order to find inhibitors of enzymes as a possible new target. A model wasbuilt by SWISS-MODEL and its quality was assessed by ERRAT, ProSA, Rampage and MolProbity servers. Docking experiments were performedand pharmacokinetics and toxicities were studied by admetSAR. Results: The predicted model was reliable to be used in docking experiments.Amentoflavone had the highest binding affinity of -10.0 Kcal/mol. Probabilities indicated that rotenone may inhibit P-glycoprotein I, hinokiflavone and silybin may inhibit P-glycoprotein II, while taspine acts on both types of P-glycoproteins. Amentofalavone, hinokiflavone, rotenone and silybin have a probability of inhibiting cytochromes that are involved in oxidation stage of metabolism. Conclusions: These compounds had binding affinities towards FMN binding site of the enzyme model and may be considered in the research for new antibacterial agents but only when their drug interactions are fully investigated.